Penyusunan Sistem Akuntansi Aliston Buana Wisata Batam - Hendra Gunawan; Eka Ayu Agustina Sari (Journal of Applied Accounting and Taxation, 2016)
The research was conducted at PT Aliston Buana Batam Tour which is engaged in tourism services. This research raises the topic of Accounting System Formulation at PT Aliston Buana Wisata Batam. The purpose of this study to find out how the accounting system in PT Aliston Buana Wisata Batam. Data collection techniques used is descriptive analysis with data collection techniques through interviews. This research provides guidance in making the recording of each transaction until the making of financial statements for PT Aliston Buana Wisata Batam can apply accounting records in every transaction and assist the accounting process.